PENYALAHGUNAAN LEM AIBON PADA ANAK: ANALISIS FAKTOR PENYEBAB DAN STRATEGI PENDAMPINGAN PASTORAL KOMPREHENSIF DI KELURAHAN KAMUNDU, KABUPATEN MERAUKE - Pranyoto, Yohanes Hendro; Berangka, Dedimus; Ndiken, Hermanus (Sekolah Tinggi Katolik Santo Yakobus Merauke, 2025)
The misuse of glue among minors is a phenomenon that is gaining increasing attention due to its serious impact on children's physical and psychological health. This study aims to identify the underlying factors that cause deviant behaviour among minors, as well as to describe the impact of glue sniffing on child development and the preventive and curative measures that can be taken. Using a descriptive qualitative approach with observation, interviews, and documentation methods, this study explores the internal, external, and social factors that contribute to glue sniffing. The research informants consisted of ten people, including glue sniffers, parents, mentors, community leaders, and environmental managers in Kamundu Village, Merauke Regency, South Papua, Indonesia. The results of the study show that the main contributing factors include a lack of supervision and attention from the family, the influence of the environment and peers, economic factors, a lack of understanding about the dangers of glue sniffing, and the easy availability of glue. The impacts experienced by children include physical growth disorders, mental disorders, and decreased cognitive function. Preventive and curative efforts involve a holistic approach that combines family guidance, community education, pastoral support from the Church, and government policies. The study concluded that addressing the problem of glue abuse requires intensive collaboration between parents, the community, the church, and the government to protect children from the adverse effects of substance abuse.